Examining The Impact Of Eia Training Program On Secondary-School English Teachers’ Classroom Practice In Bangladesh - Karim, Abdul (2019)
English teachers in Bangladesh have undergone numerous training programs. Both government-initiated and donor-sponsored training programs have been in operation in Bangladesh. Government initiated institutions to train teachers are PTIs and TTCs. However, researchers seemed to label training provided by Primary Training Institutes (PTIs) and Teacher Training Colleges (TTCs) as inadequate. Bridging the gaps intrigued government of Bangladesh to devise donor-aided training programs, including English Language Teaching Improvement Project (ELTIP), English for Teaching, Teaching for English (ETTE), Secondary Education Quality and Access Enhancement Project (SEQAEP) and Teaching Quality Improvement in Secondary Education Project (TQI-SEP). Studies reported their potential failure to bring changes in English teachers’ classroom practices. English in Action (EIA) was the last donor-funded project that incorporated school- based training program. The aim of the study was to examine the impact of EIA training program on secondaryschool English teachers’ classroom practice in Bangladesh, drawing the questions in relation to the elements learned in the training program, elements practiced in the training program and the challenges teachers faced when practicing these elements in the classroom. The present study undertook the integrated approaches to Teacher Development (TD) suggested by Hargreaves and Fullan (1992) and reflective model developed by Wallace (1991). The first research question concerned the first approach of the integrated approaches to TD.